Ameliorative Effect of Ghrelin on Thyroxin Hormones and Body Weight in Hyperthyroidism Male rats - Fouad Hamza; Muna AL-Saeed (Basrah Journal of Veterinary Research)
The study's objective is to evaluate the enhanced effect of the ghrelin on the body weight and thyroid hormones in male rats after inducing hyperthyroidism by L–thyroxin. The rats (95 males) were split into two groups. The first group consisted of 25 male rats that were given normal saline for 30 days S.C and set as a control group. While the remainder of the animals were given levothyroxine 500g/kg subcutaneously for 30 days to induce hyperthyroidism. after induction the divided into 4 groups as followe ,the first one was the control group that mentioned previously, the second group was male rats were given normal saline for 30 days S.C, the third group was male rats were given ghrelin at a dose of (0.5nmol/100μl saline) for 30 days S.C, and the fourth group was male rats (1nmol/100μl saline) for 30 days S.C.   The fifth group consisted of hyperthyroidism male rats that was given ghrelin at a dosage of (2nmol/100μl saline) for 30 days S.C. The results of final weight and weight gain are presented showed no significant difference in initial weight within all groups that were observed, while a significant decrease in final body weight in hyperthyroidism group compared with control group. On the other hand, the results revealed a significant decrease in body weight gain in male rats have hyperthyroidism compared with the control group. While the results observed a significant increase final body weight and body weight gain in all treated rats with ghrelin as compared with hyperthyroidism group. On other hand, the effect of hyperthyroidism on serum TSH, T3, and T4 concentrations revealed that the hyperthyroidism group had a significant rise in serum T3 and T4 concentrations when compared to the control group. While no significant drop in serum TSH concentration was observed in all hyperthyroidism groups handled with ghrelin (0.5, 1 and 2 nmol) as compared to the hyperthyroidism group, a significant decrease in serum T3 and T4 level was observed in all hyperthyroidism groups treated with ghrelin in comparison to the group of hyperthyroidism. Ghrelin peptide hormone and it has been shown to have potential effects on the body weight and thyroid hormone.